Low-to-moderate dose corticosteroids treatment in hospitalized adults with COVID-19. (January 2021) - Liu, Zhibo; Li, Xia; Fan, Guohui; Zhou, Fei; Wang, Yeming; Huang, Lixue; Yu, Jiapei; Yang, Luning; Shang, Lianhan; Xie, Ke; Xu, Jiuyang; Huang, Zhisheng; et al.
Abstract: Objectives: Use of corticosteroids is common in the treatment of coronavirus disease 2019, but clinical effectiveness is controversial. We aimed to investigate the association of corticosteroids therapy with clinical outcomes of hospitalized COVID-19 patients. Methods: In this single-centre, retrospective cohort study, adult patients with confirmed coronavirus disease 2019 and dead or discharged between 29 December 2019 and 15 February 2020 were studied; 1:1 propensity score matchings were performed between patients with or without corticosteroid treatment. A multivariable COX proportional hazards model was used to estimate the association between corticosteroid treatment and in-hospital mortality by taking corticosteroids as a time-varying covariate. Results: Among 646 patients, the in-hospital death rate was higher in 158 patients with corticosteroid administration (72/158, 45.6% vs. 56/488, 11.5%, p < 0.0001). After propensity score matching analysis, no significant differences were observed in in-hospital death between patients with and without corticosteroid treatment (47/124, 37.9% vs. 47/124, 37.9%, p 1.000). When patients received corticosteroids before they required nasal high-flow oxygen therapy or mechanical ventilation, the in-hospital death rate was lower than that in patients who were not administered corticosteroids (17/86, 19.8% vs. 26/86, 30.2%, log rank p 0.0102), whereas the time from admission to clinical improvement was longer (13 (IQR 10–17) days vs. 10 (IQR 8–13) days; p < 0.001). Using the Cox proportional hazards regression model accounting for time varying exposures in matched pairs, corticosteroid therapy was not associated with mortality difference (HR 0.98, 95% CI 0.93–1.03, p 0.4694). Discussion: Corticosteroids use in COVID-19 patients may not be associated with in-hospital mortality.